Dayaknese and Islam: A Confluence from Borneo's Hinterland, Indonesia - Faizal Amin; M. Ikhsan Tanggok (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2022)
Sufism has generally been regarded as the confluence that helps to facilitate Islamization in Indonesia by opening accommodating spaces for local beliefs and practices. This article examines manuscripts as historical records to show concrete examples of how Sufi interpretations of local culture are constructed. This article is not only based on philological studies of the Abang Ahmad Tahir Manuscript Collections (MSS AAT), but also observations and interviews from the field between 2012 and 2019. This article argues that the MSS AAT have provided appropriate examples of the confluence of Dayakness and Islam. Not only has MSS AAT presented dynamic engagement between critically selected local traditions of cosmology and specific elements of Sufi textual discourses, but it has also noted the ways in which such texts further indicate both the Islamisation of local communities and how they vernacularise interpretations of Islam in Kapuas Hulu, which is situated in the hinterland of West Kalimantan